Pioneers in congenital cardiac surgery: Dr. William Imon Norwood, Jr, MD, PhD. Issue 9 (24th June 2022) - Lee, Madonna E.; Kopf, Gary S.; Geirsson, Arnar; Gruber, Peter J.
Abstract: " Innovation is not only the fountainhead but the life's blood of our specialty, of surgery, of medicine, of business, or of just about anything that is progressing, evolving, and improving. In the absence of innovation there is stagnation and ultimately there is decay. Cardiac surgery, particularly congenital cardiac surgery, must continue to evolve through innovation ."